Cyclic Electron Transport around PSI Contributes to Photosynthetic Induction with Thioredoxin f - Okegawa, Yuki (Plant Physiol, 2020)
In response to light, plants efficiently induce photosynthesis. Light activation of thiol enzymes by the thioredoxin (Trx) systems and cyclic electron transport by the PROTON GRADIENT REGULATION5 (PGR5)-dependent pathway contribute substantially to regulation of photosynthesis. Arabidopsis (Arabidopsis thaliana) mutants lacking f-type Trxs (trx f1f2) show delayed activation of carbon assimilation due to impaired photoreduction of Calvin-Benson cycle enzymes. To further study regulatory mechanisms that contribute to efficiency during the induction of photosynthesis, we analyzed the contributions of PSI donor- and acceptor-side regulation in the trx f1f2 mutant background. The cytochrome b(6)f complex is involved in PSI donor-side regulation, whereas PGR5-dependent PSI cyclic electron transport is required for both donor and acceptor functions. Introduction of the pgr1 mutation, which is conditionally defective in cytochrome b(6)f complex activity, into the trx f1f2 mutant background did not further affect the induction of photosynthesis, but the combined deficiency of Trx f and PGR5 severely impaired photosynthesis and suppressed plant growth under long-day conditions. In the pgr5 trx f1f2 mutant, the acceptor-side of PSI was almost completely reduced, and quantum yields of PSII and PSI hardly increased during the induction of photosynthesis. We also compared the photoreduction of thiol enzymes between the trx f1f2 and pgr5 trxf1f2 mutants. The pgr5 mutation did not result in further impaired photoreduction of Calvin-Benson cycle enzymes or ATP synthase in the trx f1f2 mutant background. These results indicated that acceptor-side limitations in the pgr5 trx f1f2 mutant suppress photosynthesis initiation, suggesting that PGR5 is required for efficient photosynthesis induction.